The impact of empowering internal auditors on the quality of electronic internal audits: A case of Jordanian listed services companies - Hamza Alqudah; Abdalwali Lutfi; Shadi habis abualoush; Mohammad Zakaria Al Qudah; Ahmad Farhan Alshira'h; Mohammed Amin Almaiah; Mahmaod Alrawad; Magdy tork (International Journal of Information Management Data Insights, 2023)
This study emphases on the top management empowerments to internal auditors, namely, general qualification, electronic qualification and independence, affecting quality of electronic internal audits in the Jordanian Listed Service Companies. This paper used 144 usable questionnaires from internal auditors in the Jordanian listed service companies. The gathered data were analysed utilizing ``Statistical Package for Social Sciences (SPSS)''. The results reveal that general qualification, electronic qualification and independence have a significant effect on the quality of electronic internal audits, as supported by the resource-based view. Due to the importance of the service companies’ sector in the context of Jordan, the results are helpful for the internal audit profession and decision makers in offering new legislation for the internal audit profession. Future research may consider other factors that may hinder the quality of electronic internal audits, such as audit task complexity or organizational culture.